2017
DOI: 10.3343/alm.2017.37.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Accreditation on Accuracy of Diagnostic Tests in Medical Laboratories

Abstract: BackgroundMedical laboratories play a central role in health care. Many laboratories are taking a more focused and stringent approach to quality system management. In Korea, laboratory standardization efforts undertaken by the Korean Laboratory Accreditation Program (KLAP) and the Korean External Quality Assessment Scheme (KEQAS) may have facilitated an improvement in laboratory performance, but there are no fundamental studies demonstrating that laboratory standardization is effective. We analyzed the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Participation in laboratory accreditation programs could be a good alternative for monitoring and improving the overall quality of laboratory testing. Jang et al [16] reported that institutions with laboratory accreditation had significantly better EQA results over a 4-year study period for all general chemistry tests (p < 0.0001) compared to institutions without accreditation. They highlighted the importance of laboratory accreditation programs in improving laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in laboratory accreditation programs could be a good alternative for monitoring and improving the overall quality of laboratory testing. Jang et al [16] reported that institutions with laboratory accreditation had significantly better EQA results over a 4-year study period for all general chemistry tests (p < 0.0001) compared to institutions without accreditation. They highlighted the importance of laboratory accreditation programs in improving laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by Jang, Yoon and etal. 8 They studied effect of accreditation on accuracy of diagnostic tests in medical laboratories and have emphasized the necessity of establishing a system for standardization of diagnostic testing.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…6 7 In a previous study, it turned out that the result of the KEQAS had significant differences depending on the laboratories with or without KLAP. 8 However, it is unknown yet the effects of test standardization caused by the KLAP and KEQAS, so this study is intended to quantify and compare the effect of the two laboratory standardization programs on the prevalence of diabetes mellitus (DM) and impaired fasting glucose (IFG). Although the KLAP and KEQAS do not directly assess the ‘standardization’ level, they aim to pursue the standardization of laboratories through quality assurance.…”
Section: Introductionmentioning
confidence: 99%